The Protection of Freedom of Religion and Belief under Indonesia’s Criminal Code: A Normative Review of Articles 300–305 of Law No. 1 of 2023 - Syamsudin, Syamsudin; Fernando, Zico Junius (Jurnal Negara Hukum: Membangun Hukum Untuk Keadilan, 2025)
The enactment of Indonesia’s new Criminal Code (Law No. 1 of 2023) has raised critical questions regarding its impact on the protection of freedom of religion and belief (FoRB). This study seeks to answer the central question: to what extent does the new Criminal Code enhancethe legal protection of FoRB in Indonesia? Using a doctrinal  normative) legal research method, the study applies statutory, conceptual, and comparative approaches by examining the provisions of Chapter VII (Articles 300–305) in relation to international human rights standards and the previous Criminal Code. The findings indicate that the new Criminal Code refines the regulation of religious offenses by explicitly criminalizing acts of hostility, incitement to violence, and discrimination against religious groups, while offering explicit protection for minority groups, particularly adherents of indigenous beliefs. However, challenges remain regarding the interpretation and consistent enforcement of these provisions. This research contri- butes to the academic discourse on human rights and legal reform by highlighting the progressive aspects of the new legislation while critically assessing its potential limitations in practice. Abstrak Pengesahan Kitab Undang-Undang Hukum Pidana (KUHP) Baru melalui Undang-Undang Nomor 1 Tahun 2023 menimbulkan pertanyaan kritis mengenai dampaknya terhadap perlindungan kebebasan beragama dan berkeyakinan (KBB) di Indonesia. Penelitian ini bertujuan untuk menjawab pertanyaan utama, sejauh mana KUHP baru meningkatkan perlindungan hukum terhadap KBB di Indonesia?Menggunakan metode penelitian hukum normatif (doktrinal), studi ini menerapkan pendekatan perundang-undangan, konseptual, dan komparatif dengan mengkaji ketentuan Bab VII (Pasal 300–305) dan membandingkan dengan standar hak asasi manusia internasional serta KUHP sebelumnya. Temuan penelitian menunjukkan bahwa KUHP baru merumuskan tindak pidana terkait agama secara lebih terperinci dengan mengkriminalisasi tindakan permusuhan, hasutan kekerasan, dan diskriminasi terhadap kelompok agama, serta memberikan perlindungan eksplisit bagi kelompok minoritas, khususnya penganut kepercayaan lokal. Namun, tantangan masih tetap ada dalam hal interpretasi dan konsistensi penegakan hukum. Penelitian ini memberikan kontribusi terhadap diskursus akademik tentang hak asasi manusia dan pembaruan hukum, dengan menyoroti aspek-aspek progresif dalam KUHP baru sekaligus mengkritisi potensi keterbatasannya dalam implementasi.